2022
DOI: 10.1155/2022/2868904
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Milk Thistle (Silybum marianum L.) and Artichoke (Cynara scolymus L.) on Nonalcoholic Fatty Liver Disease in Type 2 Diabetic Rats

Abstract: Background. At present, nonalcoholic fatty liver disease (NAFLD) does not have an approved pharmacologic therapy. The present study investigated the protective effects and possible mechanisms of milk thistle (Silybum marianum L.) and artichoke (Cynara scolymus L.) in treating NAFLD in type 2 diabetic rats. Methods. The NAFLD was established in rats after four weeks of type 2 diabetes induction. The animals were treated with pharmaceutical preparations of milk thistle (Livergol®) and artichoke (Atheromod-B®) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The biological activities of SM include hepatoprotective (Denev et al, 2020), anticancer (Choe et al, 2020), anti-inflammatory (Fanoudi et al, 2020), immunomodulatory (Valková et al, 2021), neuroprotective (Badreddine et al, 2020) and lactogenic agent (Valková et al, 2021) in several animal species. The SM dietary supplementation had favorable effects described in mammals and birds on enhancing physiological and nutritional status over the last few decades (Doostkam et al, 2022;El Hassanen et al, 2021;Janocha et al, 2021;Stastnik et al, 2020).…”
mentioning
confidence: 99%
“…The biological activities of SM include hepatoprotective (Denev et al, 2020), anticancer (Choe et al, 2020), anti-inflammatory (Fanoudi et al, 2020), immunomodulatory (Valková et al, 2021), neuroprotective (Badreddine et al, 2020) and lactogenic agent (Valková et al, 2021) in several animal species. The SM dietary supplementation had favorable effects described in mammals and birds on enhancing physiological and nutritional status over the last few decades (Doostkam et al, 2022;El Hassanen et al, 2021;Janocha et al, 2021;Stastnik et al, 2020).…”
mentioning
confidence: 99%
“…Using an established LC–MS analysis protocol, the SMEE prepared and investigated in the present study was found to be rich in silydianin and silychristin (51.2%), whereas silybin was found to be present in a much lower amount (<10%). It is worth mentioning that all published studies on S. marianum extracts have been focusing on silymarin that is rich in silybin (50%). ,,, , Our findings may hint at yet unexplored effects of silydianin and silychristin, and therefore, more research should be concentrated on these understudied flavonolignans.…”
Section: Discussionmentioning
confidence: 79%
“…46 Also, it was demonstrated that this herbal plant can improve lipid profiles by decreasing the oxidative stress parameters that are elevated in hypercholesterolemia and by inhibiting lipid-peroxidation enzymes through flavonolignan constituents. 47 SMEE demonstrated preventive and therapeutic effects on glucose levels, as evidenced by lower FBS levels and improved results in OGTT. These findings are consistent with the antidiabetic potential of S. marianum extracts observed in previous studies.…”
Section: ■ Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Artichoke (Cynara scolymus L.), a member of the Asteraceae family, is commonly used as a healthy food and as a popular traditional herbal remedy to protect the liver function [17,18]. The active compounds identified in artichokes, including chlorogenic acid, cynarin, flavonoids and their derivatives, have attracted considerable attention for their multiple pharmacological functions, including antioxidant stress, hypolipidemic, antidiabetic, anti-inflammatory and anticancer effects [19][20][21]. Our previous study showed that artichoke water extract (AWE) has an anti-IR effect in high-fat diet-induced nonalcoholic fatty liver disease in rats [22].…”
Section: Introductionmentioning
confidence: 99%